1996
DOI: 10.1111/j.1574-695x.1996.tb00217.x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, colourimetric assay for cytotoxin activity inCampylobacter jejuni

Abstract: Cell extracts and culture supernates of Campylobacter jejuni NCTC 11168 and three isolates from faecal samples from patients with enteritis were tested for cytotoxic activity on HeLa and Vero cells using a sensitive and rapid dye reduction assay which represents a simple assay for cytotoxin activity that can be assessed visually or spectrophotometrically in the wells of microplates. The assay was as sensitive as trypan blue exclusion and did not require the use of radioisotopes. A low level of cytotoxin activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To detect and quantify cytotoxic activity during purification, we used an activity assay based on the lethal effects of the toxin on CHO cells. The TCID 50 of C31 strain for CHO cells was similar at 1–2 μg for a freshly prepared protein extract as well as a reconstituted form of the lyophilised extract as estimated by the visual method by direct microscopic observation of cytotoxic effect on cells [8] or by the indirect methyl thiazol tetrazolium (MTT) method by spectrophotometric measurement of formazin [9]. The cytotoxic effect of C31 toxin on CHO cells is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To detect and quantify cytotoxic activity during purification, we used an activity assay based on the lethal effects of the toxin on CHO cells. The TCID 50 of C31 strain for CHO cells was similar at 1–2 μg for a freshly prepared protein extract as well as a reconstituted form of the lyophilised extract as estimated by the visual method by direct microscopic observation of cytotoxic effect on cells [8] or by the indirect methyl thiazol tetrazolium (MTT) method by spectrophotometric measurement of formazin [9]. The cytotoxic effect of C31 toxin on CHO cells is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The toxin titre was expressed as tissue culture infectivity 50 (TCID 50 ) dose, the concentration of the toxin that caused cytotoxicity in 50% of the monolayer. In some instances, we used the methyl thiazol tetrazolium (MTT) assay [9] to quantitate cytotoxin activity. Metabolically active CHO cells are able to reduce the formazin present in the MTT reagent resulting in a colour change, allowing spectrophotometric quantitation of the activity of the cytotoxin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cytopathic effect correlating with cytotoxin production was confirmed by gene expression analysis in different cell cultures [ 13 , 38 , 45 ]; however, the production of enterotoxin by Campylobacter is still controversial [ 19 ]. The dominant perception is that Campylobacter enterotoxin is immunologically related to Vibrio cholere enterotoxin (CT) or Escherichia coli heat-labile enterotoxin (LT) [ 18 ]. The previous studies demonstrated that the capacity of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Enterotoxins elevate the intracellular level of cyclic adenosine monophospate, and the subsequent ion flux changes cause the excess secretion of fluid, which results in watery diarrhea. In contrast, cytotoxic activity appears to be distinct from enterotoxin activity, as cytotoxins are associated with the destruction of target cells causing mucosal inflammation and hemorrhagic reactions [ 18 , 19 ]. However, although several Campylobacter cytotoxins have been identified, only cytolethal distending toxin (CDT) has been well characterized, and it was found that CDT activity is encoded by three closely linked or slightly overlapping genes termed cdtA , cdtB and cdtC [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%